A new species of Euselasia Hübner from Meso-America and Mexico with notes on the eurypus group (Lepidoptera, Riodinidae) - Callaghan, Curtis J.; Llorente-Bousquets, Jorge; Luis-Martínez, Armando (Zootaxa, 2013)
A new species of Riodinidae, Euselasia oaxacensis Callaghan, Llorente-Bousquets & Luis-Martínez, sp. nov. from Oaxaca State in Mexico and Costa Rica is described, including its habitat, behavior and differences with other members of the eurypus group of the genus Euselasia. Notes are included in the taxonomic position, distribution and behavior of three other species of the eurypus group: Euselasia eurypus (Hewitson, 1856), Euselasia angulata (Bates, 1868); and Euselasia clesa (Hewitson, 1856).